Relaksasi Progresif Sebagai Penurun Tingkat Stres Pasien Kanker Dengan Kemoterapi - Widyastuti, Merina; Yuliastuti, Christina; Farida, Imroatul; Rinarto, Nisha Dharmayanti; Firmansyah, Iqbal Rachmad (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
Patients who undergo chemotherapy and will undergo a very risky procedure increased stress due to ignorance chemotherapy procedure that would in live or because of the condition of the disease, thus in need of appropriate measures to reduce stress levels in patients with chemotherapy. The human body responds to concerns and events that stimulate the mind and muscle tension, relaxation techniques are progressive muscle relaxing therapy. This study aimed to analyze the level of stress in cancer patients with chemotherapy in the Naval Hospital Dr. Ramelan Surabaya. This study design using one-group pre-post test design with a sample of 33 cancer patients with chemotherapy in Rumkital Dr. Ramelan Surabaya. The instrument used was a questionnaire on demographic data and questionnaire sheet DASS (Depression Anxiety Stress Scale). The test used was Wilcoxon Signed Ranks Test with significance Ï = â‰¤ 0,05. Results of measuring the level of stress before the progressive relaxation therapy is given to a range of severe stress and after being given the progressive relaxation therapy to the normal range. Test results after and before the Ï= â‰¤ 0,001 while the value of Ï= â‰¤ 0.05, then it can be concluded that there is influence progressive relaxation therapy on stress levels. This therapy is highly effective in reducing stress levels, in order to accelerate the healing process of cancer. After a given therapy, stress levels were initially high after the therapy would be a significant drop was even normal.Keywords: progressive relaxation therapy, cancer, chemotherapy, stress